RETRACTED: The role of agriculture in the socio-economic development of the Russian Far East - Egorova Amgaina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001